Analisis Potensi Longsor Menggunakan Metode Analytical Hierarchy Process pada Kecamatan Panekan, Kabupaten Magetan - Susatio, Raja; Arrisaldi, Thema; Erzagian, Egy; Hanifi Mada Mahendra, Fathan (Jurnal Ilmiah MTG, 2025)
Panekan Sub-district, Magetan Regency, is located on landslide prone area. To address this issue, a landslide susceptibility map is needed. This study aims to develop landslide susceptibility map for Panekan Sub-district using Analytical Hierarchy Process (AHP). AHP method was used to determine the weights and relative influence of five parameters which is slope, lithology, distance from structures, distance from rivers, and land use. The weight scores for each parameter are as follows: slope gradient (0,403), lithology (0,318), distance from structures (0,139), distance from rivers (0,084), and land use (0,056). Each parameter was analyzed spatially using Geographic Information System (GIS). AHP analysis produced map with values ranging from 0,99 to 4,31. Zonation was classified using the index method based on Regulation of Head of BNPB No. 2 of 2012. AHP analysis found that most areas of Panekan Sub-district are within medium hazard zone. These findings are expected to serve as a basis for local governments and communities to strengthen disaster mitigation and preparedness efforts.